KONTRIBUSI KEPEMIMPINAN KEPALA MADRASAH TERHADAP KINERJA GURU MADRASAH ALIYAH SWASTA SEKECAMATAN LINTAU BUO UTARA - Andra Endi (IAIN Batusangkar, 2016)
Contribution Leadership Head of Madrasah Aliyah to Teacher Performance of Madrasah Aliyah Sawasta in District Lintau Buo Utara. The Contribution of School Principal’s Leadership and The Performance of Private Islamic Senior High School Teacher’s at Lintau Buo Utara.On the basis of a preliminary field observation, the reseacher noticed that Private Islamic Senior High School Teachers’ performance at Lintau Buo Utara district was relatively low. It was presumed that the teachers’ low performance was caused by the ineffective leadership of the schoolThe purpose of this research was to reveal how extend the contribution of the school principal’s leadership of Private Islamic Senior High School at Lintau Buo Utara District. There were three hypotheses to be tested : 1) the school principal’s leadership contributed significantly toward the teachers’ performance; 2) simultaneously, the school principal’s leadership of Private Islamic Senior High School at Lintau Buo Utara District.The result of data analyses show that the school principal’s leadership contributed significantly (24.1%) toward the teachers’ performance toward the teachers’ performance.Kata Kunci: Kontribusi, kepemimpinan, kinerja guru